2009
DOI: 10.1097/bth.0b013e3181847652
|View full text |Cite
|
Sign up to set email alerts
|

Management of Rolando Fracture by Modified Dynamic External Fixation

Abstract: Rolando fracture is one of the most difficult fractures facing hand surgeons. It can be described as a Y- or T-shaped fracture line that runs longitudinally through the metaphyseal area, with an intra-articular fracture splitting the metacarpal base fragment into a volar and a dorsal fragment. In this study, we introduce our technique used in the management of 7 cases, which were treated by our dynamic external fixation. The results were found to be promising, with an excellent range of motion and power grip p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…However, our patient series is relatively small and randomised controlled trials are necessary to determine the optimal pin configuration. Other authors have advocated the use of relatively more complex dynamic constructs; 12,23 the excellent functional results of our series suggest such dynamic constructs have no obvious advantage over this simple, static construct.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…However, our patient series is relatively small and randomised controlled trials are necessary to determine the optimal pin configuration. Other authors have advocated the use of relatively more complex dynamic constructs; 12,23 the excellent functional results of our series suggest such dynamic constructs have no obvious advantage over this simple, static construct.…”
Section: Discussionmentioning
confidence: 78%
“…22 Previous studies have shown good outcomes with external fixation but are limited by their size (only one other series is larger than that presented here) and none have used an objective functional score. [12][13][14]21,23 The advantages of the technique described here include the use of only a single pin in the trapezium and first metacarpal respectively, and a simple, single bar, static monolateral construct (Fig 2). Previously described techniques have used two pins in either the first metacarpal, 13 the trapezium or both.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Other practitioners have utilized external fixation for Bennett or Rolando fractures: Niempoog and Waitayawinyu reported 100 percent union and good clinical results for Rolando fractures (Level IV Evidence), 26 while El-Sharkawy et al also claims good results with dynamic external fixation for Rolando fractures (Level V Evidence). 27 Like nonthumb metacarpals, no single operative fixation modality has been demonstrated to be superior to others when treating fractures of the thumb metacarpal.…”
Section: Thumb Metacarpalmentioning
confidence: 99%